Bullous Lupus: An Atypical Case of Refractory Disease in a Patient with Sulfa Allergy - Maria Salgado Guerrero; Oscar Mena Miranda; Ana B. Arevalo; Nevena Barjaktarovic; Barbara Mendez (Case Reports in Rheumatology)
Bullous systemic lupus erythematosus (BSLE) is a rare cutaneous autoimmune disorder characterized by rapid, widespread vesiculobullous lesions in patients with Systemic Lupus Erythematosus (SLE). BSLE can present as the initial manifestation of SLE and may be a marker of severe disease. In this case report, we present a case of a 22-year-old African American woman with BSLE and impaired renal function with subsequent nephrotic range proteinuria concerning for lupus nephritis and autoimmune hemolytic anemia, refractory to systemic corticosteroids, immunoglobulin, and mycophenolate mofetil, requiring dapsone after careful desensitization due to prior history of angioedema with sulfa drugs. This case highlights the importance of the prompt recognition of BSLE as the initial manifestations of SLE and illustrates the association of BSLE with severe disease and the benefit of concomitant use of dapsone with corticosteroids and other immunosuppressant drugs, even in patients with a history of sulfa allergy.